Risk Factors and Outcome of Neonates Born through Meconium Stained Amniotic Fluid in a Tertiary Hospital of Nepal - Gurubacharya, SM; Rajbhandari, S; Gurung, R; Rai, A; Mishra, M; Sharma, KR; Aryal, DR (Journal of Nepal Paediatric Society, 2015)
Introduction: The incidence of meconium aspiration syndrome is still high in the developing world contributing significantly to the neonatal mortality. The study was aimed to know the risk factors contributing to meconium aspiration syndrome and neonatal outcome in a tertiary government hospital of the country. Materials and Methods: It was a hospital based cross sectional study done over a period of three months. All live newborns born through meconium stained liquor were enrolled and all the details regarding mother, neonate were recorded. Odd’s ratio and bivariate analysis was done to assess the risk factors for meconium aspiration syndrome. Result: Out of all the deliveries 14.6% were meconium stained amniotic fluid and meconium aspiration syndrome developed in 6.6% of the neonates. Low Apgar score and premature rupture of membranes was significantly associated with the risk of occurrence of meconium aspiration syndrome. Neonates who developed meconium aspiration syndrome had mortality of 11.3%. Conclusion: Perinatal asphyxia and premature rupture of membranes were significantly associated with the development of meconium aspiration syndrome and neonates who developed meconium aspiration syndrome had high mortality. J Nepal Paediatr Soc 2015;35(1):44-48